2013
DOI: 10.1099/vir.0.054692-0
|View full text |Cite
|
Sign up to set email alerts
|

Mutation tryptophan to leucine at position 222 of haemagglutinin could facilitate H3N2 influenza A virus infection in dogs

Abstract: An avian-like H3N2 influenza A virus (IAV) has recently caused sporadic canine influenza outbreaks in China and Korea, but the molecular mechanisms involved in the interspecies transmission of H3N2 IAV from avian to canine species are not well understood. Sequence analysis showed that residue 222 in haemagglutinin (HA) is predominantly tryptophan (W) in the closely related avian H3N2 IAV, but was leucine (L) in canine H3N2 IAV. In this study, reassortant viruses rH3N2-222L (canine-like) and rH3N2-222W (avian-l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
34
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(39 citation statements)
references
References 56 publications
4
34
0
1
Order By: Relevance
“…H3N2 viruses generated by reverse genetics that contained either Trp-222 or Leu-222 were observed to have similarly small differences in receptor binding properties to those reported here, which led to the suggestion that this amino acid substitution could facilitate infection of dogs (23).…”
Section: Significancementioning
confidence: 80%
“…H3N2 viruses generated by reverse genetics that contained either Trp-222 or Leu-222 were observed to have similarly small differences in receptor binding properties to those reported here, which led to the suggestion that this amino acid substitution could facilitate infection of dogs (23).…”
Section: Significancementioning
confidence: 80%
“…The W222L mutation is located in the sialic acid receptor binding pocket, and studies have shown that HA mutations in the 220 loop can alter binding to ␣2-3-and ␣2-6-linked sialic acids (35,49,63). There is also evidence that the W222L mutation in CIV H3N2 allowed the virus to infect dogs more efficiently (64), and so the species jump and subsequent adaptation of EIV H3N8 in dogs may have been mediated by changes in receptor recognition as well. However, no infectivity differences were seen between the viruses (or the reassortants) when those were inoculated into CHO or into 6H4 cells.…”
Section: Discussionmentioning
confidence: 99%
“…The vicinal Leu222 in the seal11 HA, however, is a Trp in avian and equine A(H3N8) viruses, as well as early human A(H3N2) virus. Interestingly, Leu222 is present in canine A(H3N8) viruses and has been implicated in the adaptation of the equine viruses to a canine host (63,64), and thus, it may be similarly important in A(H3N8) virus adaptation to seals.…”
Section: Resultsmentioning
confidence: 99%